Identifying the Effective Components of HRM for Efficient Labor Capacity at Islamic Azad Universities in the North East of Iran - Yazdanpanah, Zahra; Salehi, Mohammad; Jabbari, Negin (Iranian Journal of Educational Sociology, 2022)
Purpose: The aim of the present study was to identify the Effective Components of HRM for Efficient Labor Capacity at Islamic Free Universities in the North East of Iran. Methodology: The scientific model of this research was based on a qualitative interview with the University of Azarbaijan Azad and a selective method of targeting and snowballs. Finally, by referring to the experts, 20 qualitative interviews were conducted and using the Grendard theory to identify the components of human resources management in order to attract the efficient force, the necessity of each of the extracted model components for human resources management for efficient power absorption was investigated. The research was analyzed using coding method in three stages: open, axial and selective. Findings: The results showed that the total number of nodes in non-repetitive codes was 110 in the two HRMs and 38 in the effective recruiting sector, based on the conceptual similarities of the combination of 77 nodes (common codes) in the HR department and 38 in the absorption Effective power has been extracted based on the intuition and understanding of the researchers from the subject and their share in the form of three main components related to human resources management, individual factors, organizational factors, environmental factors and 4 sub-components and efficient absorption in The template has three main components for providing employee information, delegation, payroll and 3 sub-components in the form of Tree nodes were categorized. Conclusion: The main components of human resources management include personal factors, organizational factors, environmental factors, and the three main components of employee awareness trust in employees, and to justify the findings of this research can cite theoretical foundations and previous findings.